2022
DOI: 10.3389/pore.2022.1610231
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Analysis of mTORC1/C2 and Metabolism-Related Proteins in Pediatric Osteosarcoma

Abstract: Activation of the mTOR pathway has been observed in osteosarcoma, however the inhibition of mammalian target of rapamycin (mTOR) complex 1 has had limited results in osteosarcoma treatment. Certain metabolic pathways can be altered by mTOR activation, which can affect survival. Our aim was to characterize the mTOR profile and certain metabolic alterations in pediatric osteosarcoma to determine the interactions between the mTOR pathway and metabolic pathways. We performed immunohistochemistry on 28 samples to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The improvement of the fatty acid synthesis pathway and the MVA metabolism favor rapid growth and metastasis in OS. Expression of rate‐limiting enzymes in β ‐oxidation of fatty acid is positive in approximately 90% of OS cases 68 . The PPP is a primary source of NADPH, and SSP, glutamine metabolism, FAO, and the TCA cycle can also directly or indirectly provide NADPH for anabolic reactions and redox homeostasis offering reducing capacity 139 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The improvement of the fatty acid synthesis pathway and the MVA metabolism favor rapid growth and metastasis in OS. Expression of rate‐limiting enzymes in β ‐oxidation of fatty acid is positive in approximately 90% of OS cases 68 . The PPP is a primary source of NADPH, and SSP, glutamine metabolism, FAO, and the TCA cycle can also directly or indirectly provide NADPH for anabolic reactions and redox homeostasis offering reducing capacity 139 .…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of G6PD is present in various tumors, and increased G6PD expression leads to increased biosynthesis of nucleotides and lipids necessary for cell division and proliferation, favoring tumor cell proliferation 66,67 . One study found that approximately 70% of OS samples showed high G6PD expression 68 . Wang et al.…”
Section: Glycolysis In Osteosarcomamentioning
confidence: 99%
See 3 more Smart Citations